Pengaruh Struktur Kepemilikan Keluarga, Kepemimpinan Dan Perwakilan Keluarga Terhadap Kinerja Perusahaan - Komalasari, Puput Tri; Nor, Muhammad Alfin (AKRUAL: JURNAL AKUNTANSI, 2014)
AbstractThis paper examines the impact of family ownership structure, leadership, and family representatives on firm performance that was measured by Tobinâs Q and ROA. This research used leverage, size, sales growth and firm ages of public corporate that was listed in Indonesia StockExchange for period 2009 to 2011 as control variables. Regressionâsresult shows that family ownership structure has positive impact to market performance (Tobinâs Q) and financial performance (ROA). Family CEO has negative effect to Tobinâs Q, but a positive effect to ROA. Family member on the board hasa negative effect to Tobinâs Q and ROA.